Guidelines for species descriptions of free-living aquatic nematodes: characters, measurements and their presentation in taxonomic publications - Mokievsky, Vadim; Bezerra, Tania Nara; Decraemer, Wilfrida; Eisendle, Ursula; Hodda, Mike; Holovachov, Oleksandr; Leduc, Daniel; Miljutin, Dmitry; Peña-Santiago, Reyes; Sharma, Jyotsna; Smol, Nic; Tchesunov, Alexei; et al. (Zootaxa, 2024)
Free-living aquatic nematodes are abundant, diverse and of general environmental importance. However, knowledge of species distributions of both marine and freshwater nematodes is sparse. Species distribution data are crucial for evaluating environmental impacts from human activities and to conduct integrated nematode community assessments. Basic knowledge on taxonomy and species descriptions is lacking for many regions due to decreasing taxonomic expertise, yet it is essential for biodiversity research and for building molecular sequence libraries for the application of methods such as environmental DNA. In order to encourage and facilitate taxonomic and descriptive work on this understudied group, we present here a framework for nematode species description. We begin by providing a brief overview of nematology history, then provide suggestions of microscopic methods that should be used and provide a list of characters essential for morphometric species descriptions. Finally, we briefly discuss common molecular sequencing approaches that are commonly used in nematode taxonomic literature.